Das Verhältnis von Sprache und Miteinandersein: Mit Hannah Arendt und Emmanuel Levinas im Dialog über die Horizonte eines sprachlichen Miteinanderseins - Schmitz, Vanessa (HannahArendt.net, 2022)
Talking to each other has reached its peak of the unspeakable with the question of political correctness, against which even digital communication via ’social’ networks is no match, since here we can observe more a singular firing off of comments than a dialogue in the sense of the dia-logos as a place created between and by two people talking to each other. In the attempt to revalue the dialogue as a founding moment of a reality brought forth by the human ability to form, by combining striving for an attentive-sensitive contact with the appearance of human in speaking with-one-another, the following is about an approach to the limits of a dialogical coexistence, with which the dialectic of freedom and responsibility becomes thematic in the starting point of the non-fixedness of human and finally appears as a fundamental task of human existence itself.